2009
DOI: 10.1007/s12022-009-9071-5
|View full text |Cite
|
Sign up to set email alerts
|

The Cytology of a Thyroid Granular Cell Tumor

Abstract: Granular cell tumor (GCT) of the thyroid is rare. Before this report, only four cases of thyroid GCT have been reported, none of which presented a cytopathological examination. In this paper, we report the fine needle aspiration cytology and pathological analysis of a thyroid GCT from a 12-year-old girl who presented with a painless neck mass. The tumor cells were single, in syncytial clusters, or pseudofollicles, contained small round, oval, or spindle nuclei, indistinct nucleoli, and a large amount of grayis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…GCTs are thought to arise from peripheral nerve sheath cells, but are associated with both neural and histiocytic differentiation. The cytological features previously reported are similar to our thyroid GCT findings: large cells with abundant granular cytoplasm with indistinct borders and fairly uniform, generally spherical small nuclei with inconspicuous nucleoli, and a background of naked nuclei with granular debris 3,4 …”
supporting
confidence: 88%
See 1 more Smart Citation
“…GCTs are thought to arise from peripheral nerve sheath cells, but are associated with both neural and histiocytic differentiation. The cytological features previously reported are similar to our thyroid GCT findings: large cells with abundant granular cytoplasm with indistinct borders and fairly uniform, generally spherical small nuclei with inconspicuous nucleoli, and a background of naked nuclei with granular debris 3,4 …”
supporting
confidence: 88%
“…To our knowledge, eight primary GCTs of the thyroid gland have been previously reported; only two of the reports described cytological findings obtained by fine needle aspiration (FNA). 3,4 We describe a case of thyroid GCT together with its radiological [computed tomography (CT) and sonography] and cytopathological characteristics.…”
mentioning
confidence: 99%
“…However, classic black thyroid findings include blue-gray cytoplasm with dark-brown granules and colloid can often be seen in the background. [12] Finally, because of the increased surveillance of thyroid nodules, a histiocytic reaction to a previous FNA should be considered. Histiocytes with foamy granular cytoplasm may mimic the cells of GCT, however the nuclei tend to be reniform as opposed to round and oval and the cytoplasm more foamy than granular.…”
Section: Discussionmentioning
confidence: 99%
“…GCTs of the thyroid gland are rare with only six previously reported cases in the English language literature [6][7][8][9][10][11]. Furthermore, Park et al [12] reported a case of multiple granular cell lesions in a 29-week-old male foetus involving sites such as the kidneys, gingivae and testes, as well as the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%